GROWTH, YIELD AND BIOLOGICAL INDICES OF MEDIUM DURATION PIGEONPEA (CAJANUS CAJAN L.) INFLUENCED BY INTERCROP AND DIFFERENT PLANT POPULATION - UDHAYA NANDHINI DHANDAYUTHAPANI,; L. VIMALENDRAN,; K. R. LATHA, (The Bioscan, 2015)
The study was conducted to optimize the spacing for medium duration pigeonpea at different planting geometry and row proportions under intercropped situation, during kharif, 2011 at Millet Breeding Station of TNAU, Coimbatore, India.The treatments comprised of planting geometry (row spacing of 90, 120, 150 and 180 cm at varied level of plant to plant spacing with 30, 45 and 60 cm) and different row proportions of pigeonpea + greengram (1:2, 1:3, 1:4 and 1:5). The results indicated that plant height (192.1 cm), stem girth (7.9 cm), number of branches (23.3), dry matter production (6342 kg ha-1) and yield of pigeonpea (1741 kg ha-1) were achieved higher in pigeonpea (120 x 30 cm) + greengram 1:3 row ratio. Similarly biological indices like equivalent yield (2397 kg ha-1), land equivalent ratio (1.52), area time equivalent ratio (1.15) and income equivalent ratio (1.29) were higher in aforesaid treatment. This finding with optimum plant density along with appropriate row proportion will be affordable for the pulse growing farmers.